Geopolitics of Renewable Energy: Shaping the Global Power Landscape - Mangla , Ashima (Gyan Management Journal, 2023)
This research paper provides a comprehensive analysis of the geopolitical implications of the global transition towards renewable energy. It scrutinizes the traditional energy landscape, emphasizing how fossil fuel resources have historically shaped geopolitical power structures. The key drivers of the shift towards renewables, such as climate change, economic viability, and energy security, are elaborated. The paper identifies emerging leaders in the renewable sector, namely, China and the European Union, and discusses how their strategic positioning could reshape global power dynamics. It examines the potential challenges associated with this energy transition and strategies to mitigate these challenges, emphasizing the role of international cooperation. The paper concludes that the renewable energy revolution marks a significant shift in global geopolitics. This research underscores the deep interconnection between energy and power, emphasizing its enduring relevance in this renewable future.